Primary Adenocarcinoma at Colostomy Site: Report of a Clinical Case - Sardiñas,Carlos (2022)
Abstract Colorectal cancer (CRC) is the fourth most frequently diagnosed cancer in the United States and it is found in 17% of patients thought to have complicated diverticular disease. However, primary adenocarcinoma rarely occur in the colostomy site and the risk of developing malignancy is similar to that of any other colonic segment. Polyps found in CRC screenings can be divided into the following types: hyperplastic polyps, polyps with no malignant potential, adenomatous polyps, polyps with malignant potential, and malignancies. Local complications of the colostomy can appear in the immediate, early, or late postoperative period, with an incidence ranging from 15 to 30%; neoplasia is even less common.